Extracting performances data from great piano performances : extraction of performances data - Chouw, Josephine (2016)
Older piano recordings are kept in tapes, records, or discs and will degrade over time. There are only physical recordings available because in the past, there is no technology to record music digitally, thus protecting it from time. Due to this, many great performances from the past will be lost over time. Technology today has reached a level where it is possible to keep a music recording digitally. This enables us to preserve the recordings in a perfect condition for a very long time. This project aims to preserve older piano performances recordings by converting the music recordings into a digitally synthesized music. This is done by extracting certain parameters from recordings and converts them into digital signals. The signals can then be read by music player software to play the same tune from the recording. The music pieces used in this project is recorded using a recorder in .wave (wave) file format. Using Matlab, the required parameters will be extracted from the recording and saved into a text file. This text file can be used to convert the saved parameters into MIDI (.mid) file which is the digital file format. A music player can then be used to play the converted music file.